The adenomatous polyposis coli (APC) tumour suppressor--genetics, function and disease. - Sieber, O; Tomlinson, I; Lamlum, H (2000)
Mutations in the adenomatous polyposis coli (APC) gene are the basis of familial adenomatous polyposis and the majority of sporadic colorectal cancer. APC is expressed in a wide variety of tissues, interacts with the cytoskeleton, is involved in regulating levels of beta-catenin and, most recently, has been shown to bind DNA, suggesting that it may possess a nuclear role. The mutation spectrum implicated in tumorigenesis and its correlation with disease phenotype is well characterized and has contributed to our understanding of important functional domains in APC. Despite these advances, APC continues to provide a fertile subject of research for both colorectal tumorigenesis and cancer in general.